False sanctuaries: stories from the troubled territories of South Asia - By Meenakshi Iyer (The South Asianist Journal, 2013)
The five stories in this collection capture the volatility of this region as they move through India, Pakistan, Afghanistan and Sri Lanka, tracing the fragility of lives which are affected by the divisive politics of South Asia which fragment families and societies. The stories depict displacement and loss, while capturing human tenacity and the ability to bond amongst people splintered by mindless violence.